ANALISIS LAPORAN KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PERUSAHAAN TELEKOMUNIKASI PT. SMARTFREN TELECOM TBK TAHUN 2017-2018 - Manuhutu, Yana Aprilia; Karamoy, Herman; Rondonuwu, Sintje (Universitas Sam Ratulangi, 2020)
Financial statements are the final process in the accounting process that has an important role for measuring and evaluating the performance of a company. Companies in Indonesia, especially companies that go public are required to make financial reports every period. The financial statements have the purpose of providing information about the company's financial position, performance, and cash flow which is beneficial for most report users in order to make economic decisions and show management's stewardship for the use of resources entrusted to them. This study aims to determine, the results of the analysis of Liquidity Ratios, Solviabilities, Profitability, and Activities of the financial performance of companies listed on the Indonesia Stock Exchange (Study on PT. Smartfren Telcom Tbk 2017-2018). The analytical method used is descriptive qualitative analysis. The result of this study shows that the financial performance of PT. Smartfren Telecom.Tbk is not going well yet. This is seen through the results of an analysis which shows that the instability of the company's financial performance produced between 2017 and 2018. Telecommunications companies must further improve the company's performance by reducing the amount of debt and increasing operating cash flow